Analysis of Flood Susceptibility in Adimulyo District, Kebumen Regency Year 2021 - Muryani, Chatarina; Yusup, Yasin; Rahayu, Puji (Sumatra Journal of Disaster, Geography and Geography Education, 2022)
Flood is a disaster is a large amount of puddle of water, occurs due to natural factors and human factors. Adimulyo district is one of the districts in Kebumen Regency which exposed to floods several times every year. This study aims is to analyse flood vulnerability in Adimulyo District, Kebumen Regency. This research is a quantitative descriptive research, data collection techniques in the form of field observations and secondary data analysis. Flood susceptibility analysis was carried out by overlaying maps of rainfall, soil type, elevation, slope, and distance from the area to the river. The unit of analysis uses land units. To determine the level of flood susceptibility in Adimulyo Regency, the scoring method is used. The results showed that the level of flood susceptibility in Adimulyo District was divided into 3 classes, namely 7 land units of moderate vulnerability, 54 land units of high vulnerability, and very vulnerable 13 land units.